Ethical Leadership and Knowledge Sharing: The Effects of Positive Reciprocity and Moral Efficacy. (June 2021) - Su, Xiaofeng; Lin, Wenhe; Wu, Jingjing; Zheng, Qiuqin; Chen, Xiaoxia; Jiang, Xiaoli
Despite the pivotal function of knowledge sharing for enterprises in today's highly competitive and ever-changing economic environment, the mechanism about how ethical leadership impacts employees' knowledge sharing remains a largely unexplored domain in the literature. Drawing on the social exchange theory and social learning theory, this study examines how ethical leadership helps to encourage followers' knowledge sharing behavior considering the dual-mediating effects of positive reciprocity and moral efficacy. A questionnaire-based survey is used to collect data in China. And structural equation modeling techniques are used to analyze the collected data in order to test the proposed hypothesis. Results show that ethical leadership has positive impact on followers' knowledge sharing. It is also found that both positive reciprocity and moral efficacy play significant mediating effects, and they are equally important in accounting for the impact of ethical leadership on followers' knowledge sharing. Based on the analysis results, this paper further discusses theoretical and practical implications.